2008
DOI: 10.1102/1470-7330.2008.0023
|View full text |Cite
|
Sign up to set email alerts
|

CASE REPORT: Extraskeletal Ewing sarcoma of the abdominal wall

Abstract: Ewing sarcoma is most commonly a bone tumour which has usually extended into the soft tissues at the time of diagnosis. Exceptionally, this tumour can have an extraskeletal origin. Clinical or imaging findings are non-specific and diagnosis is based on histology. We report a case of an extraskeletal Ewing sarcoma developed in the soft tissues of the abdominal wall in a 35-year-old woman who presented a painful abdominal wall tumefaction. Ultrasongraphy and computed tomography showed a large, well-defined soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Poor prognosis indicators include extraskeletal involvement and metastatic disease. Primary extraskeletal Ewing's sarcoma is a rare soft tissue tumour 4–7 …”
mentioning
confidence: 99%
“…Poor prognosis indicators include extraskeletal involvement and metastatic disease. Primary extraskeletal Ewing's sarcoma is a rare soft tissue tumour 4–7 …”
mentioning
confidence: 99%
“…However, there are several case reports or small series of extraskeletal ES/PNET with primary location in the kidney, lung, pancreas, uterus, urinary bladder, ovary, testis, parotid gland, mesenterium, skin, and subcutaneous tissue [4,5]. After an extensive literature search on the PubMed, using keywords "Ewing sarcoma, " "primitive neuroectodermal tumor, " and "abdominal wall, " we found only three cases of neoplasms in this primary location [6,7,8]. Another three cases of extraskeletal ES in the abdominal wall location were reported, but all of them were described as tumors confined to the subcutaneous adipose tissue, so we consider that they should not be included in the group of abdominal wall neoplasms [4,9,10].…”
Section: Discussionmentioning
confidence: 91%
“…After the diagnostic incisional biopsy, neoadjuvant chemotherapy was started including vincristine, cyclophosphamide, and Adriamycin for three cycles. Because of poor response to chemotherapy, surgery was required, but authors did not report any data of the follow-up [7]. Roncati et al [8] reported a third case of small extraskeletal ES/PNET measuring 1.5 cm, located in the subcutaneous tissue with deep muscle infiltration, appearing in a 45-year-old man.…”
Section: Discussionmentioning
confidence: 99%
“…In our study of 10 patients (six males, four females), the median age at diagnosis was 36.5 years. The median age across different case reports of abdominal ES/PNET have been in similar age-groups (15–35 years) [ 8 , 10 , 12 – 15 , 20 , 21 ]. National Cancer Database (NCDB) and Surveillance, Epidemiology, and End Results (SEER) database studies show that the median age of patients at diagnosis of EES is older than its skeletal counterparts and has female predilection.…”
Section: Discussionmentioning
confidence: 99%
“…ES represents the least differentiated and PNET represents the most differentiated tumors [7]. Abdominal ES/ PNETs are rare with few case reports in literature [8][9][10][11][12][13][14][15][16][17][18][19][20]. Abdominal ES/PNETs are often confused with other SRCTs such as embryonal rhabdomyosarcomas, neuroblastomas, and lymphomas.…”
Section: Introductionmentioning
confidence: 99%